Experimental Dynamical Analysis and Numerical Simulation of the Material Properties of Parts Made by Fused Deposition Modelling Technologies - Ficzere, Peter (Periodica Polytechnica Transportation Engineering, 2020)
In the recent years 3D printing became a hot topic, however it’s hard to design parts without a deep understanding of the material properties. The usage of these materials in vehicles assumes the knowledge of the behavior in dynamical environment. The aim of this study is to estimate the modal parameters and the damping properties via experimental dynamic analysis of a part made from PLA. With the results we can provide data for the FEM softwares’ input. After the numerical simulations the simulated results were compared to the measured data.